Intervensi Konseling Psikospiritual Islami untuk Mengatasi Perilaku Self-Harm Mahasiswa Muslim Indonesia - Wikan Galuh Widyarto; Muslihati Muslihati; IM Hambali; Adi Atmoko (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2026)
Self-harm behavior is a significant mental health concern among individuals in emerging adulthood, particularly university students, yet often goes undetected due to academic pressure and prevailing socio-religious norms. This study aimed to: (1) determine the prevalence and risk classification of self-harm behavior among Indonesian Muslim university students using the Self-Harm Inventory (SHI); and (2) identify appropriate guidance and counseling interventions tailored to this population. A cross-sectional survey design was employed, involving 646 undergraduate Muslim students from various higher education institutions across Indonesia. Data were collected through a self-administered online questionnaire. Results indicated that 92.7% of participants exhibited low self-harm risk, 6.3% moderate, and 0.9% high. The most prevalent forms of self-harm were psychological and spiritual in nature—such as distancing oneself from God (23.9%) and engaging in self-defeating thoughts (16.4%)—rather than physical acts like cutting (11.9%) or attempted suicide (7.7%). These findings suggest the presence of hidden psychological distress, despite the majority of respondents achieving high academic performance. The discussion underscores the necessity of holistic and contextual counseling approaches, integrating Islamic cognitive-behavioral counseling, Islamic logotherapy, and Religious Rational Emotive Behavior Therapy (Religious-REBT) as primary intervention strategies. This study recommends the development of guidance and counseling services grounded in religious values, gender sensitivity, and preventive screening mechanisms that address students’ cognitive and spiritual dimensions. The findings contribute not only to the broader understanding of self-harm within the Southeast Asian Muslim context but also support the achievement of SDGs in mental health and quality education within higher education settings.